2015
DOI: 10.1016/j.toxrep.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis hyperemesis syndrome: A case report review of treatment

Abstract: IntroductionCannabis is the most common illegal substance used in the world. The psychoactive nature of cannabis is primarily due to delta-9-tetrahydrocannabinol (THC). Some research suggests that prolonged cannabinoid use increases its half-life and fat solubility in the body, slowing gastric emptying, leading towards feelings of nausea and vomiting. We describe a case where a 32 year old male has excessive nausea and vomiting after prolonged use of daily cannabis.Case ReportA 32 year old Hispanic male with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our review of the literature identified a total of 25 case series (n = 271) and 105 individual case reports of patients identified with CHS (Table ) . Most of the reported case series and case studies predated the publication of Rome IV criteria for CHS.…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the literature identified a total of 25 case series (n = 271) and 105 individual case reports of patients identified with CHS (Table ) . Most of the reported case series and case studies predated the publication of Rome IV criteria for CHS.…”
Section: Resultsmentioning
confidence: 99%
“…From 29 case reports and case series identified on CHS presentation as of 2024, representing 36 unique individuals, the ages of people represented in cases ranged from a low of 15 years old to a high of 47 years old [6‒34]. Most reports (21 | 29) described frequency of cannabis use as daily or multiple times per day in cases.…”
Section: Characterization Of Chs Casesmentioning
confidence: 99%
“…Though only first described in 2004, cannabis hyperemesis syndrome (CHS) and affected patients' characteristic compulsive hot showering or bathing behavior has been well documented. [3][4][5][6] The physiologic cause of CHS remains poorly understood, and the mechanism of relief of symptoms that patients receive from hot water bathing and showering is even less well understood. 7…”
Section: Introductionmentioning
confidence: 99%